Intellectual capital's role in shaping corporate financial performance from a knowledge-based theory perspective - Tasrim Tasrim; Ansri Jayanti; Estiani Estiani; Tyagita Dianingtyas Sudibyo Sudibyo (Enrichment : Journal of Management, 2023)
Performance is a condition that is always a concern for managers. Conditions that are easy to "pronounce" but "difficult" to realize. This requires knowledge that exists in all components of the company. This study investigates the connection between IC and the organization's financial success. Companies in the energy categories (Oil, Gas, and Coal) listed on the Indonesia Stock Exchange make up the sample for this study (IDX). The companies selected to be sampled routinely report their financial statements from 2010-2022. In addition, the company did not suffer losses in the study period. Data is a financial statement that is then analyzed by regression analysis. The results showed that all IC items (public model) affect financial performance. However, SCE has a negative influence. This shows that the structure that the company is building allows for changes. This is because SCE is the primary support of HCE in operations.